Geospatial Weather Affected Terrain Conditions and Hazards (GeoWATCH) description and evaluation. (February 2023) - Eylander, John; Bieszczad, Jerry; Ueckermann, Mattheus; Peters, Joffrey; Brooks, Chris; Audette, William; Ekegren, Michael
Abstract: Accurately estimating soil moisture at fine resolutions – scales approaching a few meters – has been a target of a broad community involved in soil moisture research and application development, from agriculture support, improving land-atmosphere interaction in weather and climate prediction, and hydrologic modeling, to a variety of military applications. The US Army interest in high spatial-resolution soil moisture products is based on the need to better understand soil impacts on broad range of applications, including but not limited to movement and maneuver and logistics. The Geospatial Weather-Affected Terrain Conditions and Hazards (GeoWATCH) application was developed to support Army needs for high resolution soil moisture products. This paper describes the GeoWATCH application, development of the high-resolution soil moisture analysis and prediction capability, and linkages to downstream Army applications that deliver weather-informed content to support decision making. This paper also describes product evaluation and validation efforts to understand application performance. Highlights: GeoWATCH was developed to provide real-time, downscaled, globally available soil moisture products. GeoWATCH calculates high resolution soil moisture from elevation, land use and soils data with a water redistribution model. The GeoWATCH web user interface provides easy access to view and download model results. Model evaluation suggests the downscaling improves accuracy of soil moisture products from coarser resolution inputs.